METODE ISTINBATH AL-QURTHUBY DALAM PENAFSIRAN AYAT POLIGAMI - Najihah, Bannan Naelin; Jalil, Aqib Abdul (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2022)
In 2021 the divorce rate jumped to 447,743 cases due to various variants of factors, one of which was unhealthy polygamy. This study discusses the Al-Qurthuby's istinbath method in interpreting the polygamy verse to examine the ways and methods used by Al-Qurthuby to conclude the law of polygamy and interpret polygamy justice. The method used in this study uses descriptive qualitative methods with content analysis techniques. This study found that the Al-Qurthuby method in concluding the law on the interpretation of the polygamy verse used the istinbath lafdzy method in intepret amr (order) word. Like other classical Qur’anic intrepetators, Al-Qurthuby focuses on the limitation of marrying more than four wives than desciribes pologamy’s functions and he concludes that polygamy is legal on conditions that are fair.